Ladder 49 [videorecording (DVD)] - Phoenix, Joaquin; Travolta, John, 1954-; Chestnut, Morris (Touchstone Home Entertainment, 2005)
Probationary firefighter Jack Morrison matures into a seasoned veteran of the Baltimore Fire Department under the watchful eye of his mentor Chief Mike Kennedy. Responding to the worst blaze in his career, he becomes trapped inside a 20-story building. As Jack reflects on his life - seeing his first fire, bonding with fellow firefighters, the impact his job has had on his wife and kids - Chief Kennedy frantically coordinates the effort to save Jack's life.